DEVELOPMENT OF A SIMPLE LC METHOD FOR QUANTIFICATION OF LAMOTRIGINE IN HUMAN SERUM - Sigrid Mennickent; Milenka Albornoz; Marta de Diego; Gisela Ríos (Journal of the Chilean Chemical Society, 2020)
A liquid chromatographic (LC) method for quantitative analysis of lamotrigine in human serum was developed using liquid –liquid extraction with ethyl acetate. Quantitation was achieved over the concentration range of 1.0 to 40.0 µg/mL (r=0.999), using a mixture of acetonitrile: phosphate buffer (0.5 M):(69:31 v/v) as mobile phase, with a flow of 1 mL min−1. Column was C18 (150 mm x 4.6 mm, 5 cm; Merck), chloramphenicol was used as internal standard, and UV detection at α = 306 nm. The intra-assay variation was between 1.22% and 1.85% and the inter-assay was between 1.72% and 2.91%. The detection limit was 0.14 µg/mL, and the quantification limit was 0.42 µg/mL. The method proved to be accurate, with a recovery between 94.02% and 109.95 %, with a RSD not higher than 2.91 % and was selective for lamotrigine (Rs between lamotrigine and chloramphenicol vas 4.9). This method was successfully applied to quantify clozapine in patient serum samples.In conclusion, the method is precise, accurate, reproducible and selective for the analysis of lamotrigine in human serum. Therefore, it could be an important tool to evaluate drug level in this matrix and, of this way, to obtain a better drug effects.